2021
DOI: 10.1111/1365-2435.13934
|View full text |Cite
|
Sign up to set email alerts
|

Divergent contributions of living roots to turnover of different soil organic carbon pools and their links to plant traits

Abstract: Rhizodeposits and root litter contribute critically to soil organic carbon (SOC) formation and decomposition. This root‐induced SOC turnover shows great interspecific variations. Bulk SOC consists of diverse functional pools differing in formation and stabilization. Yet, it remains unclear which plant traits regulate the effects of living roots on the turnover of different SOC pools across species. By performing 13CO2 continuous labelling of six grassland species for a growing season in a climate‐controlled ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
11

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
1
4
0
11
Order By: Relevance
“…In an experiment by Jilling et al (2021), the authors observed that common root exudates (i.e., glucose and oxalic acid) caused a significant increase in turnover and potential release of C from MAOM through direct (e.g., mobilization of metal oxides) and indirect (e.g., enzyme induction) mechanisms. Similar effects were found in another field experiment by Huang et al (2021), who showed that about 70% of rhizosphere priming occurred in MAOC, which differed between species. The interspecific variations in the priming effects were explained by the differences in specific root length and root N concentration.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In an experiment by Jilling et al (2021), the authors observed that common root exudates (i.e., glucose and oxalic acid) caused a significant increase in turnover and potential release of C from MAOM through direct (e.g., mobilization of metal oxides) and indirect (e.g., enzyme induction) mechanisms. Similar effects were found in another field experiment by Huang et al (2021), who showed that about 70% of rhizosphere priming occurred in MAOC, which differed between species. The interspecific variations in the priming effects were explained by the differences in specific root length and root N concentration.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the acknowledged significance of roots in SOC accrual, their measurement is often neglected in experimental studies due to labour‐intensive efforts. Nevertheless, it is evident that both the rhizodeposits of living roots and the decomposition of dead roots contribute substantially to both MAOC and POC (Huang et al, 2021; Sokol, Kuebbing, et al, 2019; Yang et al, 2023). The predominant impact of living root inputs on the net formation of MAOC aligns with expectations from the ‘dissolved organic C (DOC)‐microbial pathway’ theory (Cotrufo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, different grassland species have distinct responses to precipitation changes and levels of resistance or resilience to drought stress [ 20 , 161 ] and consequently, plant community composition could determine ecosystem resistance or resilience to climate changes [162] . Diversity can also contribute greatly to soil C storage because species differ in the quantity and quality of plant litter and mycorrhizal C inputs, which collectively determine soil C storage [ 48 , 163 ]. Screening for species with suitable leaf and root traits, strong resistance to climate fluctuations, and complementary functions within the plant community could therefore accelerate C sequestration during grassland restoration [ 9 , 164 ].…”
Section: The Potential Contribution Of Grassland To Carbon Neutralitymentioning
confidence: 99%
“…Previous investigators reported that POM is typically considered a more temperature-sensitive indicator (Benbi et al, 2014;Georgiou et al, 2024), but such studies do not consider the rhizosphere. The rhizosphere priming effects can cause MAOM to be active (Huang et al, 2021), which poses a new challenge for us to accurately estimate M Nrec and M Nlab . Thus, there is still a need for a holistic, quantitative understanding of the patterns and controlling factors of the M Nrec and M Nlab and their effects on ecosystem N cycle.…”
mentioning
confidence: 99%